Keeping a creative sketchbook : build your artistic practice for a joyfully inspired life - Block, Emma (Running Press, 2024)
"From watercolor icon Emma Block comes a creativity guide to keeping a sketchbook as an artistic practice, with techniques and sources of inspiration for experimenting, drawing and painting, and seeing the world through a colorful lens"--